Multiplex ligation-dependent probe amplification identification of 17 different beta-globin gene deletions (including four novel mutations) in the UK population. - Gallienne, A; Dréau, H; McCarthy, J; Timbs, A; Hampson, J; Schuh, A; Old, J; Henderson, S (2009)
Large deletions of the beta-globin gene cluster are problematic to diagnose, and consequently the frequency and range of these mutations in the UK is unknown. Here we present a study evaluating the efficacy of the recently available technique of multiplex ligation-dependent prob amplification (MLPA) to determine the range and frequency of these deletions in the UK population. The results revealed a large deletion mutation in 75 of 316 patient samples collected over a 3-year period. Of these, 52 had a common (deltabeta)(0)-thalassemia [(deltabeta)(0)-thal] or hereditary persistence of fetal hemoglobin (HPFH) allele and 23 had rare or novel deletions resulting in (epsilon(G)gamma(A)gammadeltabeta)(0)-thal, (G)gamma(A)gamma(deltabeta)(0)-thal and beta(0)-thal. A total of 17 different deletions were found, 10 of which were rare and four were most likely novel [Asian Indian (epsilon(G)gamma(A)gammadeltabeta)(0)-thal, African (deltabeta)(0)-thal, African beta(0)-thal and Afghanistani beta(0)-thal]. The MLPA technique detected examples from all four categories of beta-globin gene deletions and demonstrated the wide molecular basis of deletional beta-thal/HPFH in UK patients.